Нечіткості в засобах керування мобільними роботами - Запорожець, В. А. (ХНУРЕ, 2021)
Errors and implementation inaccuracies. These are the main active attributes of all areas of hardware or software development, but the second attribute causes discomfort with the presence of the first attribute. It may suggest that no matter what problems ordinary users and highly skilled developers may encounter. An error can lead to an old solution to a problem or a new tangle of problems, which cannot be solved without researching and systematizing errors according to a certain classification.
Keywords: мобільні роботи; засоби керування; нечіткості